Biodegradation of Components of Mixture of Hydrocarbons by a Defined Pure and Consortium of Selected Hydrocarbon Degraders - Olanipekun, Ogirima Olawole; Ogunbayo, Atoke Olaide; Bello, Rahaman Adisa (Kathmandu University Journal of Science, Engineering and Technology, 2020)
The biodegradation of a mixture of aliphatic and polyaromatic hydrocarbons as multicomponent substrates in a liquid medium by pure and mixed cultures of two bacteria, Providential rettgeri and Streptococcus salivarius, two moulds, Trichoderma harzianum and Aspergillus flavipes, and one yeast, Candida famata, was investigated in this study. The microbes were isolated from petroleum hydrocarbon contaminated soil in the Niger Delta, Nigeria. The fate of the various components in the substrate was monitored individually, and each component was found to decrease during the degradation period. The degrading ability of the consortium was further studied by quantifying the growth of the culture using cumulative Carbon (vi) oxide produced and the optical density method. The rate of degradation of each hydrocarbon was monitored, and growth was observed correspondingly to the degradation of the substrates. At the end of 5 days, 86.54%, 81.85%, and 81.71% of 2-methylnaphthalene, 1-methylnaphthalene, and 1,3-dimethylnaphthalene, respectively, were degraded, while 59.65% and 73.61% of hexadecane and heneicosane, respectively, were degraded. Further degradation was obtained after 11 days, resulting in 2.36%, 3.30%, 5.90%, 6.13%, and 6.35% degradation of 2-methylnaphthalene, 1-methylnaphthalene, 1,3-dimethylnaphthalene, hexadecane, and heneicosane, respectively. Kinetic parameters such as the maximum substrate consumption rates of 0.507, 0.194, 0.798, 1.490, and 0.731 g/g/hr, and the affinities of 20.70, 6.31, 50.60, 601.0, and 358.0, were obtained for 2-methylnaphthalene, 1-methylnaphthalene, 1,3-dimethylnaphthalene, hexadecane, and heneicosane, respectively. This result showed the prospect of the defined consortium for bioremediation of multicomponent substrates.